The Effect of Comic Strip Teaching Media to the Ability of Grade Eight Students of SMP Negeri 1 Tapian Dolok In Writing A Narrative Text - Sihombing, Lisbet Novianti (Universitas Negeri Medan, 2017)
This research examined the Effect of Comic Strip Teaching Media to the Ability of Grade Eight of SMP Negeri 1 Tapian Dolok In Writing A Narrative Text.The writer formulates the problem as follow : what is the effect of comic strip teaching media to the ability of grade VIII in writing a narrative text. This research design is quantitative research that based on quasi-experimental research: the post-test only design, aimed to know the effect of technique that given, wheter it influences to the object or not. The sample of this research is taken from two classes that consists of 60 students, 30 students in experimental group in class VIII-2 and 30 students in control group in class VIII-4. The writer found that the mean of pre-test in experimental group is 65,93, post-test in experimental group is 74,37 and the mean of pre-test in control group is 60,43, post-test in control group is 65,93 and the writer also found that t-test is higher than t-table. It can be seen from df: 58 (30+30-2) with the table is 1.67 and the level of significance 0.05. It shows that t-test is higher than t-table (4,184> 1.671).After analyzing the data, the researcher concluded that Comic Strip teaching media to the ability in writing a Narrative text.